A grain texture model to investigate effects of grain shape and orientation on macro-mechanical behavior of crystalline rock. (December 2021) - Zhao, Xianyu; Elsworth, Derek; He, Yunlong; Hu, Wanrui; Wang, Tao
Abstract: Grain texture characteristics play vital roles in modulating the anisotropy, strength, and ductility of crystalline rock. Grain textures (shape, size, orientation and heterogeneity) are a key parameter controlling response but are challenging to incorporate in a quantitative manner. We propose and incorporate a grain texture model (GTM) into granular mechanics modeling by the distinct element method (DEM). This model seeds then grows individual non-spherical grain clusters that honor the granular and intergranular textures of granites. The model is applied to "virtually sinter" Lac du Bonnet granite and represent the pre-through post-peak evolution of damage and deformation. The model is able to capture all significant features of this macroscopic mechanical evolution of damage through failure. With an increase in confining pressures, a transition from brittle to ductile response occurs in the post peak stage and the fitted Hoek-Brown strength envelopes for peak strength and crack-initiation stress in these numerical experiments are consistent with physical observations. An increase in aspect ratio of individual grains slightly increases the UCS/TS ratio, whereas an increase in dip angle decreases the UCS/TS ratio. Parametric studies varying the proportion of minerals and the form of contact groups with various grain shapes and orientations allow the systematic evaluation of controls of grain texture on the evolving macroscale strength and deformability. An increase in grain aspect ratio increases the proportion of inter-grain contacts. A change in dip of the grain long-axis does not change the balance of either the mineral groups or the contact groups but significantly influences the number of inter-grain tensile cracks and the resulting UCS/TS ratio.